Challenges and Strategies of Women in Local Governance during the COVID-19 Pandemic: A Phenomenological Study - Lumintao, Jornie; Baulete, Elaine; Palomares, Perla; Hussien, Eucil (Jurnal Pemerintahan dan Kebijakan (JPK), 2025)
Scholarship on women in political leadership during the COVID-19 pandemic highlights their notable effectiveness in crisis governance. While some scholars attribute this to gendered traits, others point to institutional, political, and economic factors. However, limited research has examined the lived experiences of women leaders to understand what drives their crisis responses. This study addresses that gap by exploring how women at the local level, specifically women Punong Barangays (PBs) in Bukidnon Province, Philippines, perceived their leadership roles during the pandemic, focusing on the challenges they faced and the strategies they employed to overcome them. Using a phenomenological approach, data were collected through key informant interviews with purposive and snowball sampling. Data triangulation and ethical procedures, including informed consent, ensured validity and reliability. Thematic collation analysis revealed that women PBs encountered non-cooperation from residents, health risks, resource shortages, organizational constraints, emotional and physical strain, and role conflicts. To navigate these, they employed strategic communication, community education, and local partnerships to foster cooperation and address immediate needs. Effective resource management, personal resilience, and strong support networks, including family and faith, were instrumental in sustaining their efforts. Ultimately, these women viewed their leadership as a mandated duty, driven by commitment to public service and their close connection to grassroots communities. Findings suggest that women’s effectiveness in crisis leadership stems not only from gendered attributes but also from motivations such as civic responsibility, community proximity, and emotional strength. The study contributes to rethinking women’s political leadership in decentralized governance and offers insights for policy reforms to better support local women leaders beyond gendered expectations.